A Retrospective Comparative Analysis of Titanium Mesh and Custom Implants for Cranioplasty. Issue 1 (13th September 2019) - Rosinski, Clayton L; Patel, Saavan; Geever, Brett; Chiu, Ryan G; Chaker, Anisse N; Zakrzewski, Jack; Rosenberg, David M; Parola, Rown; Shah, Koral; Behbahani, Mandana; Mehta, Ankit I
Abstract: BACKGROUND: Autologous bone removed during craniectomy is often the material of choice in cranioplasty procedures. However, when the patient's own bone is not appropriate (infection and resorption), an alloplastic graft must be utilized. Common options include titanium mesh and polyetheretherketone (PEEK)-based custom flaps. Often, neurosurgeons must decide whether to use a titanium or custom implant, with limited direction from the literature. OBJECTIVE: To compare surgical outcomes of synthetic cranioplasties performed with titanium or vs custom implants. METHODS: Ten-year retrospective comparison of patients undergoing synthetic cranioplasty with titanium or custom implants. RESULTS: A total of 82 patients were identified for review, 61 (74.4%) receiving titanium cranioplasty and 21 (25.6%) receiving custom implants. Baseline demographics and comorbidities of the 2 groups did not differ significantly, although multiple surgical characteristics did (size of defect, indication for craniotomy) and were controlled for via a 2:1 mesh-to-custom propensity matching scheme in which 36 titanium cranioplasty patients were compared to 18 custom implant patients. The cranioplasty infection rate of the custom group (27.8%) was significantly greater ( P  = .005) than that of the titanium group (0.0%). None of the other differences in measured complications reached significance. Discomfort, a common cause of reoperation in the titanium group, did not result in reoperation in any of the patients receiving custom implants. CONCLUSION: Infection rates are higher among patients receiving custom implants compared to those receiving titanium meshes. The latter should be informed of potential postsurgical discomfort, which can be managed nonsurgically and is not associated with return to the operating room.